Learning Empowerment, Resistance and Female Identity Development from Popular Television: Trans-women Tell Stories of Trans-formation - Robin Redmon Wright (Adult Education Research Conference, 2007)
This paper explores how and why three British trans-women, who were biologically male when they watched The Avengers in 1962-1964, engaged in self-directed learning while modeling part of their new female identity on the character of Dr. Cathy Gale.